Changes in peripheral chemoreflex sensitivity during sustained, isocapnic hypoxia. - Bascom, D; Clement, I; Cunningham, D; Painter, R; Robbins, P (1990)
One hypothesis concerning the origin of hypoxic ventilatory decline is that hypoxia acts centrally to depress peripheral chemoreflex loop activity. To investigate possible changes in peripheral chemoreflex loop activity during sustained, isocapnic hypoxia, the ventilatory responses to four one minute pulses of either extra hypoxia (45 Torr) or carbon dioxide (8 Torr above resting levels) were measured in man at minutes 2, 7, 12, and 17 of a 23 min isocapnic, hypoxic period (50 Torr). For hypoxia, the first pulse response (130%) was significantly greater (P less than 0.05) than the fourth response (74%). For CO2, pulse responses 2 and 3 (101 and 103%, respectively) were significantly greater (P less than 0.05) than the fourth response (91%). A central depression of peripheral chemoreflex loop activity should affect peripheral sensitivities to CO2 and hypoxia equally. Our results suggest that the peripheral sensitivity to hypoxia declined more than that to CO2, implying a peripheral chemoreceptor origin for hypoxic ventilatory decline.